2013
DOI: 10.1155/2013/610721
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance in Wheat

Abstract: Drought is one of the most important phenomena which limit crops' production and yield. Crops demonstrate various morphological, physiological, biochemical, and molecular responses to tackle drought stress. Plants' vegetative and reproductive stages are intensively influenced by drought stress. Drought tolerance is a complicated trait which is controlled by polygenes and their expressions are influenced by various environmental elements. This means that breeding for this trait is so difficult and new molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
212
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(226 citation statements)
references
References 148 publications
(151 reference statements)
5
212
1
8
Order By: Relevance
“…Based on these findings, we propose that both avoidance and tolerance features are crucial for drought resistance under severe drought stress in sesame. Similar conclusions were reported on several important crops including cowpea [41] and wheat [42].…”
Section: Drought Avoidance and Tolerance Are Required For Resistance supporting
confidence: 86%
“…Based on these findings, we propose that both avoidance and tolerance features are crucial for drought resistance under severe drought stress in sesame. Similar conclusions were reported on several important crops including cowpea [41] and wheat [42].…”
Section: Drought Avoidance and Tolerance Are Required For Resistance supporting
confidence: 86%
“…In other cases, similar sensitivity between vegetative and reproductive period was observed in wheat as reduction in the number of ears in wheat was reported when drought occurred during the entire growing season or between 2 0 anthesis and early milk development, but not during grain maturity (Sieling et al, 1994). Another review had suggested that wheat yield loss could be substantially greater if drought occurred during tillering (47%) than during booting (21%) (Nezhadahmadi et al, 2013). This was particularly true when grain yield only considered that produced by the normal tiller rather than the combination of late and normal tiller (Mogensen et al, 1985).…”
Section: Phenological Phasementioning
confidence: 64%
“…In fact; TCC is an important factor in determining the photosynthetic rate and dry mater production [73][74][75]. The pronounced effect of water levels on TCC at post-anthesis might be due to the changes in photosynthetic rate, which is parallel to the change of chlorophyll content during grain filling [76].…”
Section: Total Chlorophyll Content (Tcc) and Canopy Temperature Deprementioning
confidence: 99%